Impact of neem cake amendment in the casing soil on control of Trichoderma aggressivum Samuels & W. Gams and Lycoriella ingenua (Dufour) and mushroom yield: Neem cake in mushroom production - Drobnjaković, Tanja; Luković, Jelena; Milijašević-Marčić, Svetlana; Todorović, Biljana; Stepanović, Miloš; Potočnik, Ivana; Rekanović, Emil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The study was focused on improvement of the integrated management strategy against green mould disease agent Trichoderma aggressivum Samuels & Gams and mushroom fly Lycoriella ingenua (Dufour) as pests of the white button mushroom Agaricus bisporus (Lange) Imbach. The impact of neem cake amendment in casing soil on regulation of the abundance of mushroom sciarid fly adults, efficacy in controlling the green mould disease agent, and mushroom yield was evaluated. Casing soil was supplemented with different concentrations of neem cake: 1, 2.5, 5, 10 and 15%. Neem cake added as a supplement to casing soil at a rate of 2.5% reduced the number of mushroom fly adults by 83.93% and green mould disease incidence by 59.6% in comparison to the control. No adverse effect on mushroom formation, yield and quality of fruiting bodies was observed at that concentration. Amendment of 2.5% neem cake in the casing soil could be recommended for application in mushroom production to control L. ingenua and symptoms of green mould disease without negative impact on mushroom yield.
Keywords: Agaricus bisporus; Azadirachta indica; green mould disease; mushroom fly